(1RS,2RS)-4,4′-(1-Azaniumyl-2-hydroxyethane-1,2-diyl)dipyridinium tetrachloridoplatinate(II) chloride - Miguel Parra-Hake (Acta Crystallographica Section E, 2013)
The title compound, (C12H16N3O)[PtCl4]Cl, consists of a 4,4′-(1-azaniumyl-2-hydroxyethane-1,2-diyl)dipyridinium trication, a square-planar tetrachloridoplatinate(II) dianion and a chloride ion. In the cation, the pyridinium rings attached to the central 1-azaniumyl-2-hydroxyethane fragment have an anti conformation, as indicated by the central C—C—C—C torsion angle of −166.5 (6)°, and they are inclined to one another by 63.5 (4)°. In the crystal, the cations and anions are linked through N—H...Cl and O—H...Cl hydrogen bonds. There are also π–π contacts [centroid–centroid distances = 3.671 (4) and 3.851 (4) Å] and a number of C—H...Cl interactions present, consolidating the formation of a three-dimensional supramolecular structure.